Effects of water depth gradient on physiological characteristics of Vallisneria natans. Issue 1 (1st January 2019) - Cao, Yun; Chen, Dan; Ji, Xin-Sheng; Zhang, Su-Juan; Huang, Qi; Wang, Wen-Lin
Abstract: For the purpose of studying the response of the Vallisneria natans antioxidant enzyme defense system to different water depths, we selected seedlings with well-preserved rhizomes, consistent germination and positive growth as experimental plants and put them into 10 plexiglass barrels at depth gradients. After 60 days of simulation experiments, we tested the malondialdehyde (MDA), superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), chlorophyll and soluble protein contents and root activity. The results showed that (1) the contents of Chla, Chlb, Chl (a + b) and Car first increased with water depth and then decreased, reaching maximum values of 0.99, 0.38, 1.37 and 0.20 mg/g, at 110 cm respectively; (2) SOD and POD decreased with increased water depth, with a significant decreasing trend particularly between 30 and 60 days, and MDA showed the same trend as POD. CAT decreased with increased water depth but then showed a two-fold increase trend, probably due to the gradual effects of long-term water stress the antioxidant enzyme system in V. natans leaves. (3) Soluble protein had the same trend as MDA. Root activity implied that the more active the root system is, the more ramets and biomass are produced. In this experiment, the plant grew well at depths of less than 120 cm and showed clear signs of aging or death beyond this depth; the results showed that the antioxidant enzyme defense system engaged a series of antioxidant protection mechanisms to increase plant stress resistance ability and reduce or eliminate the damage of plants, but when the stress increased beyond the tolerance of the plant, the antioxidant defense system was destroyed, which eventually led to the death of the plant.